Rapid virtual training and field deployment for COVID-19 surveillance officers: experiences from Ethiopia - Wang, Shu-Hua; Yimer, Getnet; Bisesi, Michael; Lisawork, Leuel; Sugerman, David; Alayu, Mikias; Wossen, Mesfin; Abayneh, Sisay Alemayehu; Gallaghe, Kayleigh; Endashaw, Tigist; Kubinson, Hannah; Kanter, Theresa; et al. (The Pan African medical journal, 2022)
Rapid scale-up of surveillance activities is the key to successful coronavirus disease 2019 (COVID-19) pandemic prevention and mitigation. Ethiopia did not have a sufficient number of active surveillance officers for the public health COVID-19 response. Training of surveillance officers was needed urgently to fill the gap in the workforce needed. Subject-matter experts from the United States and Ethiopia developed applicable training modules including background on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), contact investigation, and communications. The training modules were delivered live in real-time via web-based virtual presentation. Seventy-seven health surveillance officers were hired, trained, and deployed in two weeks to assist with surveillance activities in Ethiopia. Electronic capacity building is needed in order to improve Web-based training in resource-limited settings where internet access is limited or unreliable. Web-based synchronously delivered course was an effective platform for COVID-19 surveillance training. However, strengthening public and private information technology capacity, literacy, and internet availability will improve Web-based education platforms in resource-limited countries.Rapid scale-up of surveillance activities is the key to successful coronavirus disease 2019 (COVID-19) pandemic prevention and mitigation. Ethiopia did not have a sufficient number of active surveillance officers for the public health COVID-19 response. Training of surveillance officers was needed urgently to fill the gap in the workforce needed. Subject-matter experts from the United States and Ethiopia developed applicable training modules including background on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), contact investigation, and communications. The training modules were delivered live in real-time via web-based virtual presentation. Seventy-seven health surveillance officers were hired, trained, and deployed in two weeks to assist with surveillance activities in Ethiopia. Electronic capacity building is needed in order to improve Web-based training in resource-limited settings where internet access is limited or unreliable. Web-based synchronously delivered course was an effective platform for COVID-19 surveillance training. However, strengthening public and private information technology capacity, literacy, and internet availability will improve Web-based education platforms in resource-limited countries.